Sleep Laboratory Test Referrals in Canada: Sleep Apnea Rapid Response Survey. Issue 1 (2014) - Evans, Jessica; Skomro, Robert; Driver, Helen; Graham, Brian; Mayers, Irvin; McRae, Louise; Reisman, Joseph; Rusu, Corneliu; To, Teresa; Fleetham, John
Abstract : BACKGROUND: An estimated 5.4 million Canadian adults have been diagnosed with sleep apnea or are at high risk of experiencing obstructive sleep apnea (OSA). There are no recent Canadian data regarding access to and predictors of referral for diagnostic testing in these populations. METHODS: The Sleep Apnea Rapid Response survey sampled 8647 Canadian adults and captured information about risk, testing, diagnosis and treatment of sleep apnea. Predictors of sleep laboratory test referrals were assessed using log-linked binomial regression modelling. Information regarding sleep testing facilities was updated at the provincial and regional levels. RESULTS: Approximately 76.8% (95% CI 70.1% to 83.6%) of adult Canadians with sleep apnea and 5.1% (95% CI 3.4% to 6.7%) of those at high risk for OSA reported being referred to a sleep laboratory. Significant predictors of sleep laboratory referral in the general population were male sex, middle age, overweight or obese, a chronic condition, having a regular medical doctor and reporting symptoms of sleep apnea. Region of residence was also a predictor of reported sleep laboratory referral, with individuals from Ontario being more likely to report being referred to a sleep laboratory versus individuals from other regions. CONCLUSION: Individuals reporting risk factors and symptoms associated with OSA were more likely to report a sleep laboratory testing referral compared with those without risk factors or symptoms. However, Canada's diagnostic sleep laboratory testing capacity varies across regions and is believed to be inadequate given the number of individuals at high risk for OSA who did not report testing referral.